2008
DOI: 10.1002/mds.21773
|View full text |Cite
|
Sign up to set email alerts
|

Moving ear syndrome: The role of botulinum toxin

Abstract: We report a 30-year-old man with moving ear syndrome caused by focal myoclonic jerks of the right temporal muscle. This focal myoclonus would disappear while the patient was sleeping, swallowing, or speaking. He was treated with botulinum toxin type A with a favorable outcome. Previous reports of this condition and possible therapeutic approaches are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…Our patient presented with a 3 months history of bilateral auricular myoclonus, a period that is within the range that is reported in the literature. As with other reported cases, our patient could not voluntarily suppress her auricular movements, 1 , 7 , 9 and the movements disappeared completely during sleep. 1 , 3 , 6 , 9 …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our patient presented with a 3 months history of bilateral auricular myoclonus, a period that is within the range that is reported in the literature. As with other reported cases, our patient could not voluntarily suppress her auricular movements, 1 , 7 , 9 and the movements disappeared completely during sleep. 1 , 3 , 6 , 9 …”
Section: Discussionsupporting
confidence: 80%
“…With regards to the laterality, auricular myoclonus has been equally distributed in patients, unilateral in some 4 , 8 , 9 and bilateral in others. 1 , 3 , 6 , 7 , 10 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Three major muscles located around the auricle, namely the anterior, superior, and posterior auricular muscles, are functionally vestigial in humans. Previous studies have shown that ear movement disorders can successfully be treated with botulinum toxin injections [2,5,7]; however, to date, there have been no reports on surgical treatment. Herein, we report a patient with auricular dystonia, which was refractory to botulinum toxin injections, who was successfully treated with unilateral pallidothalamic tractotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Ear aurical muscle myoclonusis an extremely rare phenomenon. Publications define it with various terms: ear tic, moving ear syndrome, muscle dystonia, ear dyskinesia [23][24][25][26][27]. Ear aurical muscle myoclonus, as it appears from one of the titles, is often accompanied by its evident rhythmical movement, yet as a rule it disappears at bedtime and at breath hold [10].…”
Section: Introductionmentioning
confidence: 99%